Generasi Z Dan Politik Viral: Analisis Semiotik Simbol “Joget Gemoy” Dalam Diskursus Kampanye Politik 2024 - Anggun Zellen Medista; Anita Marianata (CV. ITTC INDONESIA, 2024)
This article discusses the phenomenon of “Joget Gemoy” in Prabowo Subianto's political campaign, which went viral among Generation Z ahead of the 2024 presidential election in Indonesia. The issue is raised on how entertaining communication strategies can influence political image communication towards young voters' engagement. The purpose of this study is to analyze the impact of Prabowo's political branding through viral content on social media, particularly the Tiktok application. The method used is a qualitative approach with content analysis, which includes primary and secondary data collection from interactions on the Tiktok platform. The results of this study show that Prabowo from a stern and rigid figure became more familiar and funny and managed to attract the attention of Gen Z in increasing his electability. This research emphasizes the importance of understanding the dynamics of young voters in a political context where social media as an effective tool plays a role in building political support.